FREEDOM AT 250: UKRAINIAN AMERICAN DEMOCRATIC DIALOGUE - Kaluzna, Julia (Young Scholars Grinchenko – Seton International Journal, 2026)
The concept of freedom has been an important part of the United States for a long time. For generations, freedom has been portrayed as both a political principle and a promise that anyone could pursue, achieve, and live out. This promise is often captured in the idea of the “American Dream”, which suggests that through hard work and determination, individuals can build better lives for themselves, regardless of their background. For many immigrants, this vision has served as a source of hope, drawing people from around the world to a country that defines itself as a provider of opportunity and freedom. In this sense, the United States has not only come to symbolize freedom, but has also represented the possibility of advancement and the ability to shape and improve one’s own future.